MODEL DAN PENERAPAN KOMUNIKASI ORGANISASI PENDIDIKAN ISLAM - Ika Hartika (Hijri, 2017)
Education as a system is an organization that aims to create graduation which have multi-intelligence so it can manifest themselves as part of civil society.To achieve the goals of education above, Communication within organization is an important element of that forms and allows an organization to work. The fact in the field of attention of Madrasah to communication is very low. This research will discuss about Model and Application of Islamic Education Organization Communication (A Research in MAN I Takengon, Aceh Tengah, Aceh). This research aims to descriptive of the model and application of organization communication. This research used a qualitative approach, the data collected through observation, in-depth interviews, and documents about various communication models used, then analyzed data, by describing qualitatively using the concept of miles and Huber man. The research’s result shows that the communication model used varies, no ones of model of communication is superior. Communication tools are both internal and external relatively the same, the used of information powerless computing or ICT has not been maximized. It is not significant obstacles are found in establishing internal and external communications, although the committee and parents are not proactive in establishing communication with the Madrasah.